Early anti IL-1 treatment replaces steroids in refractory Kawasaki disease: clinical experience from two case reports - Maria Vincenza Mastrolia (Therapeutic Advances in Musculoskeletal Disease, 2021)
Refractory Kawasaki disease (KD) is related to a major risk of coronary arteries abnormalities and its treatment is not standardized. In this regard, anakinra (ANA), an interleukin (IL)-1 receptor antagonist, represents an emerging therapeutic option. We report two cases of children, diagnosed with KD, nonresponsive to two doses of intravenous immunoglobulins, successfully treated with ANA, without a prior use of steroids. Patient 2 developed a coronary dilatation, that improved significantly after ANA therapy. Our experience highlights IL-1 blockade effectiveness in reducing KD inflammation and suggests ANA adoption as second-line therapy, with a timesaving and steroid-sparing strategy. Our results, combined with the evidence of the IL-1 key role in KD and coronary arteritis pathogenesis and to the recent clinical evidence reported by the KAWAKINRA trial, encourage an earlier recourse to ANA in patients with refractory KD, in order to fight inflammation, and to treat and prevent the development of coronary artery aneurysms. Further studies are needed to better define the place of IL-1 blockade in KD step-up treatment.